Novelties introduced by the Council of Europe Convention on preventing and combating violence against women and domestic violence - Samardžić, Sandra; Kovaček Stanić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Violence as a phenomenon inherent to man, from the outset, can be manifested in different forms. According to statistics, the number of women who have suffered some form of violence is disturbingly great. Domestic violence and violence against women is a serious problem on which work on an international level has recently began. Some international organizations indirectly dealt with this issue in instruments which refer to the protection of human rights. At the European level, in 2011, the Convention of the Council of Europe (so-called Istanbul Convention), was adopted which was the first legally binding instrument on the European continent, that deals with the prevention of violence against women, protection of them and punishing the perpetrators. The Convention entered into force in 2014, and Serbia is one of the countries that have ratified this Convention. This paper aims to presents novelties that will be brought to the domestic legal system by this convention, with simultaneous analysis of the situation in Montenegro, where in 2010 the Law on Protection against Domestic Violence was enacted.